Grain Boundary Engineering for Achieving High Thermoelectric Performance in n‐Type Skutterudites. Issue 13 (17th February 2017) - Meng, Xianfu; Liu, Zihang; Cui, Bo; Qin, Dandan; Geng, Huiyuan; Cai, Wei; Fu, Liangwei; He, Jiaqing; Ren, Zhifeng; Sui, Jiehe
Abstract : Grain or phase boundaries play a critical role in the carrier and phonon transport in bulk thermoelectric materials. Previous investigations about controlling boundaries primarily focused on the reducing grain size or forming nanoinclusions. Herein, liquid phase compaction method is first used to fabricate the Yb‐filled CoSb3 with excess Sb content, which shows the typical feature of low‐angle grain boundaries with dense dislocation arrays. Seebeck coefficients show a dramatic increase via energy filtering effect through dislocation arrays with little deterioration on the carrier mobility, which significantly enhances the power factor over a broad temperature range with a high room‐temperature value around 47 μW cm −2 K −1 . Simultaneously, the lattice thermal conductivity could be further suppressed via scattering phonons via dense dislocation scattering. As a result, the highest average figure of merit ZT of ≈1.08 from 300 to 850 K could be realized, comparable to the best reported result of single or triple‐filled Skutterudites. This work clearly points out that low‐angle grain boundaries fabricated by liquid phase compaction method could concurrently optimize the electrical and thermal transport properties leading to an obvious enhancement of both power factor and ZT . Abstract : Low‐angle grain boundaries with dense dislocation arrays in Yb‐filled CoSb3 fabricated by the liquid phase compaction could simultaneously contribute to the energy filtering effect and strong phonon scattering. Both high power factor and high average figure of merit ZT over a broad temperature range could be finally realized, comparable with all previous studies of advanced filled Skutterudites.